Development of a reference database for assessing dietary nitrate in vegetables - Blekkenhorst, L.; Prince, R.; Ward, Natalie; Croft, K.; Lewis, J.; Devine, A.; Shinde, S.; Woodman, R.; Hodgson, J.; Bondonno, C. (Wiley - V C H Verlag GmbH, 2017)
Scope: Nitrate from vegetables improves vascular health with short-term intake. Whether this translates into improved long-term health outcomes has yet to be investigated. To enable reliable analysis of nitrate intake from food records, there is a strong need for a comprehensive nitrate content of vegetables database. Methods and results: A systematic literature search (1980-2016) was performed using Medline, Agricola and Commonwealth Agricultural Bureaux abstracts databases. The nitrate content of vegetables database contains 4237 records from 255 publications with data on 178 vegetables and 22 herbs and spices. The nitrate content of individual vegetables ranged from Chinese flat cabbage (median; range: 4240; 3004-6310 mg/kg FW) to corn (median; range: 12; 5-1091 mg/kg FW). The database was applied to estimate vegetable nitrate intake using 24-h dietary recalls (24-HDRs) and food frequency questionnaires (FFQs). Significant correlations were observed between urinary nitrate excretion and 24-HDR (r = 0.4, P = 0.013), between 24-HDR and 12 month FFQs (r = 0.5, P < 0.001) as well as two 4 week FFQs administered 8 weeks apart (r = 0.86, P < 0.001). Conclusion: This comprehensive nitrate database allows quantification of dietary nitrate from a large variety of vegetables. It can be applied to dietary records to explore the associations between nitrate intake and health outcomes in human studies.